The Role of Tradition and Culture on Population Patterns in Gonda Baru Village - Sudiah, Lismawati; Masdiana, Masdiana; Ersiliya, Lely (Journal of English Language and Education, 2026)
This study discusses the limited understanding of the role of tradition and culture in shaping the population pattern of the community in Gonda Baru Village, Sorawolio District, Baubau City. Local traditions and culture are believed to have a significant influence on the pattern of marriage, birth, death, and population mobility, but scientific studies on this matter are still rare. This study aims to find out the extent to which tradition and culture play a role in determining the population pattern of the people in the region. The method used is qualitative research with data collection techniques through observation, in-depth interviews, and documentation. Respondents consisted of traditional leaders, village officials, and communities selected by purposive sampling. The results of the study show that local traditions, such as marriage customs, kinship systems, birth rituals, and death ceremonies, are still very influential in regulating population patterns. This tradition has an impact on the high rate of young marriages, limited control over the number of births, and strong social ties in managing migration and population mobility. In addition, the available infrastructure also affects people's mobility patterns, but cultural values remain the dominant factor. Tradition and culture play an important role in shaping the population pattern in Gonda Baru Village, both in terms of marriage, birth, death, and mobility. Therefore, development policies and population planning in this region need to consider local wisdom so that the programs designed can run effectively and in accordance with the cultural values of the community.